2022
DOI: 10.29313/bcsms.v2i1.390
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Antara Ukuran Tumor dan Gradasi Histopatologi dengan Metastasis Kelenjar Getah Bening pada Penderita Kanker Payudara di RSUD Al-Ihsan Provinsi Jawa Barat

Abstract: Abstract. Breast cancer is a malignancy that occurs in the epithelial tissue of the lobules or ducts of the breast glands. The majority of breast cancer patients come in an advanced stage, which impacts the patient's prognosis. The prognosis of breast cancer can be seen from various prognostic factors. This study aimed to analyze the relationship between tumor size and histopathological gradation with lymph node metastases in breast cancer patients. This cross-sectional study was conducted at Al-Ihsan Hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This grading system is significant in predicting cancer prognosis, as the grade reflects the speed at which the tumor grows and its potential to spread. It is influenced by various factors, including genetic mutations, growth factors produced by the tumor, and signaling pathways related to cell growth and division [41]. This difference is also influenced by the expression of hormone receptors such as ER, PR, HER2, and Ki67.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This grading system is significant in predicting cancer prognosis, as the grade reflects the speed at which the tumor grows and its potential to spread. It is influenced by various factors, including genetic mutations, growth factors produced by the tumor, and signaling pathways related to cell growth and division [41]. This difference is also influenced by the expression of hormone receptors such as ER, PR, HER2, and Ki67.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the results of this study showed a significant relationship between the degree of differentiation and LVI (p < 0,001). Indira et al [41] in their research found a relationship between histopathological grading and a significant incidence of LVI (p = 0,039) in breast cancer in Bandung, West Java. Houvenaeghel et al [43] in 2021 also found that the incidence of LVI was significantly related to hormone receptor status, tumor subtype, and grade.…”
Section: Declarationsmentioning
confidence: 91%